The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21186914
|View full text |Cite
|
Sign up to set email alerts
|

Classifications of Neurodegenerative Disorders Using a Multiplex Blood Biomarkers-Based Machine Learning Model

Abstract: Easily accessible biomarkers for Alzheimer’s disease (AD), Parkinson’s disease (PD), frontotemporal dementia (FTD), and related neurodegenerative disorders are urgently needed in an aging society to assist early-stage diagnoses. In this study, we aimed to develop machine learning algorithms using the multiplex blood-based biomarkers to identify patients with different neurodegenerative diseases. Plasma samples (n = 377) were obtained from healthy controls, patients with AD spectrum (including mild cognitive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…A meta-analysis [ 27 ] illustrated that non-steroidal anti-inflammatory drugs (NSAIDs) are efficient for the treatment as well as prevention of PD and may also lead to a decrease in the neutrophil count. An immunomagnetic reduction method (IMR) was used to detect the dynamic changes in blood biomarkers [ 14 ], and it was found that plasma α-synuclein in PD patients was greater significantly compared with that in the healthy group of control and was the highest in Parkinson’s disease dementia (PDD) patients. Moreover, monocytes were found to be closely related to α-SYN in the course of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis [ 27 ] illustrated that non-steroidal anti-inflammatory drugs (NSAIDs) are efficient for the treatment as well as prevention of PD and may also lead to a decrease in the neutrophil count. An immunomagnetic reduction method (IMR) was used to detect the dynamic changes in blood biomarkers [ 14 ], and it was found that plasma α-synuclein in PD patients was greater significantly compared with that in the healthy group of control and was the highest in Parkinson’s disease dementia (PDD) patients. Moreover, monocytes were found to be closely related to α-SYN in the course of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the diagnosis of PD and its differentiation from other neurodegenerative diseases rely mainly on neurological symptoms and psychological cognitive function assessments, magnetic resonance imaging, positron emission tomography (PET) and other methods [ 13 ]. In addition, other groups have developed a blood-based classifier that includes Aβ40, total Tau, and a-syn levels to monitor the progression of PD, and α-synuclein levels were shown to have high specificity and accuracy in this effort [ 14 ]. However, the relatively high cost of monitoring these levels may limit its large-scale practical application in middle-aged and elderly populations.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning can also help to identify features that are important for disease progression or serve as markers for clinical trials (Ithapu et al, 2015 ). In addition to harvesting brain imaging data [especially the multimodality imaging data from the public ADNI database ( http://adni.loni.usc.edu/ )], deep learning has been applied to biospecimens (Lee et al, 2019b ; Lin et al, 2020 ), electronic health records (Landi et al, 2020 ; Nori et al, 2020 ), speech (Lopez-de-Ipina et al, 2018 ), neuropsychological data (Choi et al, 2018 ; Kang et al, 2019 ), and a combination of MRI and neuropsychological data (Qiu et al, 2018 ; Duc et al, 2020 ). By contrast, few studies have applied deep learning to cognitive task data, which – by design – is supposed to be more sensitive to detect early and mild neurocognitive impairment (Locascio et al, 1995 ; Perry and Hodges, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study was supported by two other investigations reporting increased sensitivity (80–86%) and specificity (82%) of the Aβ 42 /pTau181 ratio, suggesting that those proteins are the best biomarker subset to differentiate FTLD from AD ( 37 , 170 ). The plasma levels of p-Tau181 were significantly higher in patients on the AD spectrum groups and FTD patients, with the highest level in the FTD group ( 171 ). In a recent study, plasma p-tau181 distinguished AD of DFT with an AUC of 100% ( 172 ).…”
Section: Resultsmentioning
confidence: 93%